Evidence-Based Cesarean Section for Universal Use in China: The "Stark (Misgav Ladach) Method". Issue 1 (July 2019) - Stark, Michael
Abstract : Abstract: There are many ways to perform cesarean section, with many methods developing from local traditions. Following a 3-year study process, a modified, evidence-based method has been developed, which is now in use in many countries. The abdomen incision is based on the Joel-Cohen incision, the peritoneum is opened by repeated stretching, and the uterus is opened transversely after pushing the bladder down. After delivery the uterus is sutured with one layer using a large needle, and the abdomen is closed with only two layers, fascia and skin. This method was subject to scores of studies, with all upholding its superiority over traditional methods. As a result, the "Stark (Misgav Ladach) method" is recommended to become a standard procedure across China.